Big data in healthcare made simple to save people's lives. (18th February 2022) - Anand, R. Vijay; Meenakshisundaram, Iyapparaja; Jothikumar, R.; Chaitanya, P. Krishna
In healthcare system, big data is playing an important role in predicting the outcome of the disease, prevention and to handle the effect of such additional disorders or diseases by transience and saving the cost of medical treatment. Many countries diagnose the diseases using big data and it is playing a main role for information generation to identify the diseases. The main focus of large information has started out and a few tasks were installed a place to share information about patient's scientific records and perceive their records amongst fashionable public, non-public hospitals and clinics. However, there are many challenges in conducting huge facts in healthcare, particularly in relation to privacy, protection, requirements, authority, integration of statistics, save the statistics, classify the data and to combine the generation. Its miles authoritative that these challenges to be overcome before huge facts can be implemented effectively in healthcare.